2009
DOI: 10.1016/j.otohns.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Primary versus secondary tracheoesophageal puncture in salvage total laryngectomy following chemoradiation

Abstract: There is an increased risk of PCF in patients undergoing primary TEP compared with secondary TEP following chemoradiation. No difference in acquisition of speech fluency was identified between the two groups. Patients undergoing primary TEP achieved fluent speech 62 days sooner than their secondary TEP counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 11 publications
(54 reference statements)
8
78
0
5
Order By: Relevance
“…Regarding this subject, 6 articles analyzed the TEP, and the incidence of fistulas was not configured as a risk factor ( p = 0.69 and I 2 = 86%). When studies that led to high heterogeneity were removed [13,15], we observed the same effect obtained above ( p = 0.48 and I 2 = 20; Fig. 6).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Regarding this subject, 6 articles analyzed the TEP, and the incidence of fistulas was not configured as a risk factor ( p = 0.69 and I 2 = 86%). When studies that led to high heterogeneity were removed [13,15], we observed the same effect obtained above ( p = 0.48 and I 2 = 20; Fig. 6).…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, this is a complication easily resolved with no surgical intervention [14]. Emerick et al [13] found no difference in their series as regards infection among groups and this is very similar to data found by others [9,10,11], with slightly higher numbers of infection in the surgical wound in TEP1 when compared to TEP2, however, with no statistical significance. In contrast, Shenoy et al [12] found no occurrence of wound infection in their series.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…4,5 The advantages of tracheoesophageal speech valves over oesophageal speech include: immediate voice, high success rates and the ability to sustain speech with a more fluent quality than that achieved with oesophageal speech. 4,5 It is essential for the valve to have a good fit as this ensures both a water-and air-tight seal, thereby maximising voice quality and reducing the risk of aspiration and valve displacement. Leakage, both through the centre of the valve and around the periphery, is a common problem, occurring in up to 27 per cent of patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Primary TEP with intraoperative prosthesis placement has been associated with earlier voice acquisition, is safe and has higher rates of successful voice rehabilitation as compared to secondary TEP. 2,[3][4] Successful voice outcomes have also been reported in primary TEP with laryngopharyngectomy that require advanced reconstruction techniques, such as free tissue transfer. 4,5 The supraclavicular artery island flap (SCAIF) is an effective alternative to free tissue transfer and is being used with increasing frequency after laryngectomy.…”
Section: Introductionmentioning
confidence: 99%